Methane source linked to gas hydrate system at hydrate drilling areas of the South China Sea: Porewater geochemistry and numerical model constraints. (December 2018) - Hu, Yu; Luo, Min; Chen, Linying; Liang, Qianyong; Feng, Dong; Tao, Jun; Yang, Shengxiong; Chen, Duofu
Highlights: Porewater geochemistry of two piston cores in hydrate drilling areas was investigated. A numerical model was applied to quantify involved biogeochemical processes. Methane consumed mainly originated from external sources rather than local methanogenesis. The external methane is most likely to originate from local gas hydrate systems. Abstract: Methane of various origins is widespread in the sediments of continental margins, representing a key component of the carbon cycle in the ocean. Its occurrence in shallow marine sediments can be linked to the gas hydrate reservoir in the deep sedimentary column. However, this type of methane is difficult to track due to complex reactions occurred during its long distance migration. Porewater geochemical analyses of two ∼7 m piston cores (D17-15 and W01-16) combined with a reaction-transport model were applied to quantify methane-related biogeochemical processes and to explore the linkage of shallow methane to gas hydrate reservoir in the hydrate drilling areas of Shenhu and Dongsha in the South China Sea (SCS). The model results revealed that anaerobic oxidation of methane (AOM) is the predominant biogeochemical process in both cores, consuming approximately 85% and 74% of sulfate in the modeled domain, respectively. The crossplot of dissolve inorganic carbon (DIC) accumulation versus sulfate depletion of the system suggests that methane consumed during the AOM is mainly originated from external methane sources rather than local methanogenesis. Using a δ 13 CDIC mass balance calculation together with model-derived fractions of different DIC sources, we estimated that the δ 13 C value of the external methane in core D17-15 is −66.6‰, which is in accordance with the previous reported δ 13 C values of hydrate-bound methane in the area. These results suggest that methane consumed in shallow sediments in the hydrate drilling areas of the SCS is mainly originated from local gas hydrate reservoir. The proposed approach has the potential to be used to differentiate the sources of methane, which will provide constraints on dynamics of methane in gas hydrate-bearing marine sediments.